COMMERCIAL SYSTEM WITH SPECIAL REFERENCE TO E-COMMERCE, ITS PROS & CONS - Shyju (International Journal of Research -GRANTHAALAYAH, 2016)
E-commerce or Electronic commerce is a methodology of modern business, which addresses the requirements of business organizations. It can be broadly defined as the process of buying or selling of goods or services using an Electronic Medium such as the Internet. A person sitting on his chair in front of a computer can access all the facilities of the internet to buy or sell the products. Traditional commerce that is carried out physically with effort of a person to go and get products. E-commerce has made it easier for human to reduce physical work and to save a lot of time. Even though it gives a lot of advantages to the economy, it faces some demerits mainly in the case of security. Security is the challenge facing E-commerce today. With the invention of E-commerce there is the possibility for B to B business, business through ads in YouTube, through website, mobile commerce, Electronic Fund Transfer, supply chain management, internet marketing, online transaction process etc..Even though with merits and demerits, E-commerce is in a developing stage.